Pirminių veiksmažodžių kirčiavimas - Pakerys, Antanas (Kalbotyra, 1996)
Prosodic types of principal forms of standard Lithuanian primary verbs are connected with its phonetic and morphological characteristics, i. e.: sounds consisting syllable nuclei of routes; endings of stems in present and past lenses; sounds which arc available between nuclei and endings of stems (in present and past lenses) or suffix -ti (in infinitive). In addition, comparison of primary verbs with -(s)tyti mixed-type verbs is helpful. In some cases the relation between accentuation and semantics is established.